Islamic perspective of Sociology and Anthropology: a definition - Md. Noon, Hazizan (International Institute of Islamic Thought and International Islamic University Malaysia, 2017)
In many writings and works on Islam and Muslims, the phrase ‘Islamic perspective’ is used quite frequently to indicate that the view put forward or expressed on an issue or topic represents or is based on Islamic teachings. In various literatures, the phrase ‘Islamic perspective’ has been employed in both singular and plural forms. What does Islamic perspective mean then? Is there only one Islamic perspective on an issue or are there many Islamic perspectives? What is the implication of this dual usage of the phrase for the readers’ understanding of an issue? Since this edited work also employs the term ‘Islamic perspective’ in its title and that its chapters are written with this in mind but by different authors, this chapter attempts to explore the use of this term in contemporary discourses and works with a hope that it will clarify some issues over its usage and subsequently reduce the possible misunderstandings among readers. The work basically examines the variation in the use of Islamic perspective and highlights the essence, common principles and spirit of all ‘Islamic perspectives’ to that form their common foundation and outlook.